1993
DOI: 10.1007/bf00749959
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fertilizer P residues in a calcareous vertisol

Abstract: The amounts of available P in a Typic Pellustert containing different levels of residual fertilizer P were assessed in a field experiment and chemically with cation-anion-exchange resin, using: (i) P desorbed after 1 extraction, (ii) cumulative P from 8 extractions [Resin8-P] and (iii) the asymptote of the extraction curve. P exchangeable to 32p, Olsen-P and P extracted by dilute salt solution (0.03 M KC1) were also measured. P available to sorghum in 1989 was strongly influenced by fertilizer P applied in 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…Therefore, the highest surface area of smectite and/or hydroxides of iron and aluminium with no positive sites plays a small role in the adsorption of added negatively charged phosphate ions in vertisols. This supports the ICRISAT's classical experimental observations on P adsorption and desorption on vertisols (Kasireddipalli soils), which clearly indicate that P adsorption is not a major problem in the vertisols and that all the adsorbed P is easily exchangeable by P 32 and a small amount of P is adsorbed in the non-exchangeable form (Sahrawat and Warren, 1989;Shailaja and Sahrawat, 1994;Warren and Sahrawat, 1993). ICRISAT (1988) envisaged that CaCO 3 could adsorb P because the effective sorption by CaCO 3 is not well understood, and P adsorption is not always related to CaCO 3 content (Goswami and Sahrawat, 1982); perhaps the critical factor here is the quality of the CaCO 3 .…”
Section: Phosphorussupporting
confidence: 79%
“…Therefore, the highest surface area of smectite and/or hydroxides of iron and aluminium with no positive sites plays a small role in the adsorption of added negatively charged phosphate ions in vertisols. This supports the ICRISAT's classical experimental observations on P adsorption and desorption on vertisols (Kasireddipalli soils), which clearly indicate that P adsorption is not a major problem in the vertisols and that all the adsorbed P is easily exchangeable by P 32 and a small amount of P is adsorbed in the non-exchangeable form (Sahrawat and Warren, 1989;Shailaja and Sahrawat, 1994;Warren and Sahrawat, 1993). ICRISAT (1988) envisaged that CaCO 3 could adsorb P because the effective sorption by CaCO 3 is not well understood, and P adsorption is not always related to CaCO 3 content (Goswami and Sahrawat, 1982); perhaps the critical factor here is the quality of the CaCO 3 .…”
Section: Phosphorussupporting
confidence: 79%
“…Among the soils from Great Britain, resin P, which is one measure of plant‐available P (Somasiri and Edwards, 1992), was always greater in the fertilized (G3, G6, and G9) than the unfertilized (G2, G5, and G8) soils. Previous research has shown that long‐term fertilization increases plant‐available P in soils, as measured by extraction with ion exchange resins (Warren and Sahrawat, 1993). Water‐soluble P ranged from 0.1 mg kg −1 in G2 to 20.8 in D3 mg kg −1 Differences in the sorption properties between soils are clearly evident; for example, the G soils contained little WSP relative to the other soils and relative to their resin‐extractable P contents.…”
Section: Resultsmentioning
confidence: 99%
“…The soil samples collected before sowing the ryegrass and after the ®nal harvest were analysed for isotopically exchangeable P (P e ) by the method of Warren & Sahrawat (1993).…”
Section: Plant and Soil Sampling And Analysismentioning
confidence: 99%